The Moral Message Of Islam In The Song Of Setan Pasti Kalah By Rhoma Irama: An Analysis Of Aqidah And Morals - Pratama, M. Arifky; Latief, Saefudin; Permatasari, Iin; Nursyamsiah; Arikarani, Yesi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This study aims to examine the Islamic moral message in Rhoma Irama's song